Gambaran Pengetahuan dan Keterampilan Mahasiswa Sarjana Keperawatan Semester 8 Tentang Bantuan Hidup Dasar di Universitas ‘Aisyiyah Surakarta - Syafrani Nurul Islamiyah; Fida’ Husain (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Background: Emergencies can occur anywhere and anytime, including when natural disasters occur, this first aid is very important to save victims. Based on the vision and mission of Bachelor of Nursing Study Program which excels in disaster, BHD skills must be possessed in dealing with emergency events as prospective medical personnel. Research objective: To determine the knowledge and skills of 8th semester nursing students regarding basic life support at 'Aisyiyah University, Surakarta. Aim: To describe the knowledge and skills of 8th-semester nursing students regarding Basic Life Support at 'Aisyiyah University Surakarta. Methods: This study design is descriptive research using a cross-sectional technique, sample of 62 respondents from the 8th semester students of 'Aisyiyah University Surakarta. Results: Of the 62 respondents, the knowledge level about BHD was predominantly adequate in 45 respondents (72.4%) and good in 17 respondents (27.4%). The skill level in performing BHD was predominantly not passing in 38 respondents (61.3%), with passing skills in 24 respondents (38.7%). Conclusion: From 62 students, the results showed that the average student had a sufficient level of knowledge and skills that had not yet passed.